2009
DOI: 10.2478/v10007-009-0003-1
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and pharmacological investigation of novel 4-(3-ethylphenyl)-1-substituted-4H-[1,2,4]triazolo[4,3-a] quinazolin-5-ones as a new class of H1-antihistaminic agents

Abstract: The first generation antihistamines penetrate the blood brain barrier and also possess anticholinergic properties; this has led to the development of a second generation of H 1 -antagonists such as terfenadine, cetirizine and astemizole (1). A common feature of the first generation compounds includes two aryl or heteroaryl rings linked to an ali-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(25 citation statements)
references
References 7 publications
0
25
0
Order By: Relevance
“…Derivatives of [1,2,4]triazolo[4,3-a]quinazolin-5(4H)-one showed the H1-antihistaminic [1][2][3][4][5][6][7][8][9], anticonvulsant [10], antiHIV [11], anticancer [12], anti-asthmatic [8,13], antiallergic [13], anti-inflammatory [13, 14] bioactivities. 1-Alkyl-3-aryl [1,2,4]triazolo[4,3-a]quinazolin-5(4H)-ones demonstrated moderate antibacterial [11,12] including antitubercular [12] and antifungal [11] properties.…”
Section: Analysis Of Recent Studies and Publications In Which A Solutmentioning
confidence: 99%
“…Derivatives of [1,2,4]triazolo[4,3-a]quinazolin-5(4H)-one showed the H1-antihistaminic [1][2][3][4][5][6][7][8][9], anticonvulsant [10], antiHIV [11], anticancer [12], anti-asthmatic [8,13], antiallergic [13], anti-inflammatory [13, 14] bioactivities. 1-Alkyl-3-aryl [1,2,4]triazolo[4,3-a]quinazolin-5(4H)-ones demonstrated moderate antibacterial [11,12] including antitubercular [12] and antifungal [11] properties.…”
Section: Analysis Of Recent Studies and Publications In Which A Solutmentioning
confidence: 99%
“…Derivatives of [1,2,4]triazolo [4,3-a]quinazolin-5(4H)-one are representatives of important class of condensed heterocycles possessing wide biological activity range. Among their potential pharmacologically significant properties, the antibacterial [2,10,13], antitubercular [2,13], antifungal [2,10], anti-HIV [2], antihistaminic [3,4,5,6,14,15], anticonvulsant [1], anticancer [13], antiasthmatic [12,14], antiallergic [12], anti-inflammatory [11,12] bioactivities should be mentioned. Hence, it was of interest to check some [1,2,4]triazolo [4,3-a]quinazolin-5(4H)-one derivatives against tropical disease protozoa.…”
Section: Introductionmentioning
confidence: 99%
“…Among their potential pharmacologically significant properties, the antibacterial [2,10,13], antitubercular [2,13], antifungal [2,10], anti-HIV [2], antihistaminic [3,4,5,6,14,15], anticonvulsant [1], anticancer [13], antiasthmatic [12,14], antiallergic [12], anti-inflammatory [11,12] bioactivities should be mentioned. Hence, it was of interest to check some [1,2,4]triazolo [4,3-a]quinazolin-5(4H)-one derivatives against tropical disease protozoa. The aim of this study was to evaluate [1,2,4]triazolo [4,3-a]quinazolin-5(4H)-one derivatives containing an amide group that was connected to 1 position of triazoloquinazoline moiety via sulfur-carbon or carbon chain against tropical parasitic protozoa Leishmania, Plasmodium and Trypanosoma.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compound ( [66][67][68]. It was found that by varying substitution over the first position of the triazolo quinazoline (52) ring there was variation in the biological activity.…”
Section: Compound 50mentioning
confidence: 99%